Effects of primary metabolites of organophosphate flame retardants on transcriptional activity via human nuclear receptors. (14th March 2016) - Kojima, Hiroyuki; Takeuchi, Shinji; Van den Eede, Nele; Covaci, Adrian
Highlights: Nuclear receptor activities of 12 OPFR-metabolites were studied by cell-based assays. HO- m -TPHP and HO- p -TPHP showed more potent ERα/β agonistic activity than did TPHP. These HO-TPHPs also acted as PXR agonists as well as ERβ, AR and GR antagonists. Diester OPFR-metabolites and BCIPHIPP did not show any receptor activity. Abstract: Organophosphate flame retardants (OPFRs) have been used in a wide variety of applications and detected in several environmental matrices, including indoor air and dust. Continuous human exposure to these chemicals is of growing concern. In this study, the agonistic and/or antagonistic activities of 12 primary OPFR-metabolites against ten human nuclear receptors were examined using cell-based transcriptional assays, and compared to those of their parent compounds. As a result, 3-hydroxylphenyl diphenyl phosphate and 4-hydroxylphenyl diphenyl phosphate showed more potent estrogen receptor α (ERα) and ERβ agonistic activity than did their parent, triphenyl phosphate (TPHP). In addition, these hydroxylated TPHP-metabolites also showed ERβ antagonistic activity at higher concentrations and exhibited pregnane X receptor (PXR) agonistic activity as well as androgen receptor (AR) and glucocorticoid receptor (GR) antagonistic activities at similar levels to those of TPHP. Bis(2-butoxyethyl) 3′-hydroxy-2-butoxyethyl phosphate and 2-hydroxyethyl bis(2-butoxyethyl) phosphate act as PXR agonists at similar levels to their parent, tris(2-butoxyethyl) phosphate. On the other hand, seven diester OPFR-metabolites and 1-hydroxy-2-propyl bis(1-chloro-2-propyl) phosphate did not show any receptor activity. Taken together, these results suggest that hydroxylated TPHP-metabolites show increased estrogenicity compared to the parent compound, whereas the diester OPFR-metabolites may have limited nuclear receptor activity compared to their parent triester OPFRs.